Unraveling InSAR Observed Antarctic Ice-Shelf Flexure Using 2-D Elastic and Viscoelastic Modeling - Wild, Christian T.; Marsh, Oliver J.; Rack, Wolfgang (Frontiers in Earth Science, 2018)
Ice-shelf grounding zones link the Antarctic ice-sheets to the ocean. Differential interferometric synthetic aperture radar (DInSAR) is commonly used to monitor grounding-line locations, but also contains information on grounding-zone ice thickness, ice properties and tidal conditions beneath the ice shelf. Here, we combine in-situ data with numerical modeling of ice-shelf flexure to investigate 2-D controls on the tidal bending pattern on the Southern McMurdo Ice Shelf. We validate our results with 9 double-differential TerraSAR-X interferograms. It is necessary to make adjustments to the tidal forcing to directly compare observations with model output and we find that when these adjustments are small (<1.5 cm) a viscoelastic model matches better, while an elastic model is more robust overall. Within landward embayments, where lateral stresses from surrounding protrusions damp the flexural response, a 2-D model captures behavior that is missed in simple 1-D models. We conclude that improvements in current tide models are required to allow for the full exploitation of DInSAR in grounding-zone glaciology.